An interdisciplinary platform for information behavior research in the liberal arts hobby. Issue 5 (2nd September 2014) - Hartel, Jenna
Abstract : Purpose: – The liberal arts hobby is a leisure pursuit that entails the systematic and fervent pursuit of knowledge for its own sake. The purpose of this paper is to introduce the liberal arts hobby as a setting for information behavior research. Design/methodology/approach: – The method of interdisciplinary translation work is used to relate existing research from the specialties of leisure studies, adult education, and information behavior. Drawing from leisure studies, the liberal arts hobby is presented within the context of the serious leisure perspective, a theoretical framework of leisure. Also, relevant research. Findings: – The basic informational features of the liberal arts hobby and adult learning project are discussed in terms of three issues of current interest within information behavior scholarship. The issues are: first, social metatheory and the ideal level of analysis; second, time and information behavior; and third, information behavior in pleasurable and profound contexts. Research limitations/implications: – Research into everyday life, serious leisure and hobbies is extended and methodological tools are provided. Practical implications: – Information professionals, such as public librarians or systems designers, will have a better understanding of the information experience of a popular hobby group and be better able to meet their information needs. Social implications: – Awareness and understanding of the liberal arts hobby will be increased across the field of information science, thereby creating a better alignment between the field and society. Originality/value: – The paper is the first to establish an interdisciplinary starting point for information behavior research in the liberal arts hobby.